Effects of scavengers of Criegee intermediates and OH radicals on the formation of secondary organic aerosol in the ozonolysis of limonene. (August 2017) - Ahmad, W.; Coeur, C.; Cuisset, A.; Coddeville, P.; Tomas, A.
Abstract: The ozonolysis of limonene was investigated in a laminar aerosol flow reactor under dry conditions enabling the first nucleation/condensation steps to be studied. The effect of scavengers of stabilized Criegee Intermediates (sCI) and OH radicals on secondary organic aerosol (SOA) formation was evaluated in terms of particle size distribution, aerosol mass and yield, as well as nucleation threshold. Depending on the experimental conditions, SOA yields between 0.08 and 0.64 were observed corresponding to SOA masses of 7.5–542 µg m −3, respectively, which is in good agreement with the literature. The presence of a sCI scavenger, namely acetic acid or acetone, significantly delayed the onset of the particle formation and led to much lower SOA masses, with a stronger effect of acetic acid than acetone. Particle numbers were also drastically reduced by the presence of these two sCI scavengers. The observed effects were attributed to the reactions of the limonene sCI with the scavengers, stressing the crucial role of the sCI chemistry in the formation of SOA from limonene ozonolysis. From an atmospheric point of view, the present results underline the role of the environmental conditions in the SOA formation, especially the presence of carbonyls and organic acids even at moderate concentrations (a few hundreds of µg m −3 ). Likewise, the presence of an OH-radical scavenger (1-butanol or toluene) significantly lowered SOA masses and particle numbers. This effect was attributed to changes in the OH reaction products as well as in the peroxy radical chemistry and indicated the role of the hydroperoxide channel in the formation of SOA in the limonene ozonolysis. Thus, the present study provides the first evidence of the role of both sCI and RO2 chemistry in the nucleation processes leading to the SOA formation in the limonene reaction with O3 . Highlights: First steps in the formation of secondary organic aerosol from limonene ozonolysis were investigated. Acetic acid and acetone delay secondary organic aerosol formation and strongly reduces aerosol mass and yield. Leading role of both stabilized Criegee Intermediates and peroxy radicals in the formation of secondary organic aerosol was assessed.